Accountants' Index/Bibliography of Accounting and Tax Articles (Book). - Cannon, Arthur M.; Gregory, Robert H. (The Accounting Review, 1954)
Reviews two books on accounting. "Accountants' Index, Tenth Supplement"; "Bibliography of Accounting and Tax Articles," by Cecil E. Coe.